ANIMATION DESIGN ABOUT ANTI-CORRUPTION FOR 4TH TO 6TH GRADE STUDENTS - Abdalla Sesari, Mohammad
The design of this work aims to prevent the increase in the number of corruptors and criminal acts of corruption by planting anti-corruption characters in the younger generation. The reason of this design is because corruption is still common in Indonesia, especially in government. Now the government has realized that to support the success of corruption eradication agendas, it is not enough just to take action but be supported by preventive actions. This is indicated by the signing of Presidential Regulation Number 54 of 2018 concerning National Strategy for Corruption Prevention by President Joko Widodo. The Ministry of Education and Culture decided to play a role in preventing corruption through education. The method chosen by the Ministry of Education and Culture is to incorporate the values of anti-corruption education into subjects in schools. According to numbers of child psychologists, elementary school students in grades 3-6 still cannot be taught about anti-corruption directly because their mind has not yet developed there. What can be taught is character education in their daily lives and parents and teachers play a very important role because they are the two figures most often involved in children's daily lives. Educating children can be done using various media and one of them is animation media. Cartoons are the most watched television programs by children in Indonesia. Children are more interested in cartoon content than traditional learning methods, because cartoons have well-written scenarios, supported by audio and colored visual effects that can leave an impressive impression on children. Animation designed for elementary school children in grades 4-6, the story should be as simple as possible, funny and gives positive impression to the child. For animations that leave messages and impressions for children, the easiest example is Disney's animated Pinocchio. In the animation the character receives the direct impact of his bad behaviour, which is Pinochio’s nose gets longer when he lies. The concept of causation is what inspired me in designing this animation. The author wants to convey a message that instills the value of anti-corruption characters through stories in this animation. The character values that want to be presented are honesty, accountability, caring and cooperation. The author realizes there are still many shortcomings both in writing and design work due to the lack of knowledge and experience of students. Therefore the author apologizes for the incompleteness of this final project. Even so, the authors still hope that the work of this final project can still be useful for academics and the wider community.